Handbook of Iris Recognition - Burge, Mark J.; Bowyer, Kevin W.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
More than 100 trillion iris comparisons are now being performed on a daily basis, a number that is rapidly growing. This is breath-taking progress for a field that is arguably just twenty years old. The first book of its kind devoted entirely to the subject, the Handbook of Iris Recognition introduces the reader to this exciting, rapidly developing, technology of today and tomorrow. Blending insights from the editors$1 (Bown work, and exploiting their broad overview of the field, this authoritative collection introduces the reader to the state of the art in iris recognition technology. Topics and features: With a Foreword by the (3z(Bfather of iris recognition,(3y (BProfessor John Daugman of Cambridge University Presents work from an international selection of preeminent researchers, reflecting the uses of iris recognition in many different social contexts Provides viewpoints from researchers in government, industry and academia, highlighting how iris recognition is both a thriving industry and an active research area Surveys previous developments in the field, and covers topics ranging from the low-level (e.g., physics of iris image acquisition) to the high level (e.g., alternative non-Daugman approaches to iris matching) Introduces many active and open areas of research in iris recognition, including cross-wavelength matching and iris template aging This comprehensive text/reference is an essential resource for anyone wishing to improve their understanding of iris recognition technology, be they practitioners in industry, managers and executives, or researchers searching for new insights and ideas. Dr. Mark J. Burge is Senior Principal Scientist at the MITRE Corporation, McLean, VA, USA. Dr. Kevin W. Bowyer is the Schubmehl-Prein Family Professor and Department Chair of Computer Science and Engineering at the University of Notre Dame, IN, USA.s
Introduction to the Handbook of Iris Recognition -- A Survey of Iris Biometrics Research: 2008-2010 -- Standard Iris Storage Formats -- Iris Quality Metrics for Adaptive Authentication -- Quality and Demographic Investigation of ICE 2006 -- Iris Recognition with Taylor Expansion Features -- A Theoretical Model For Describing Iris Dynamics -- Iris Recognition in the Visible Wavelength -- Multispectral Iris Fusion and Cross-spectrum Matching -- Robust and Secure Iris Recognition -- Template Aging in Iris Biometrics -- Fusion of Face and Iris Biometrics -- Methods for Iris Segmentation -- Introduction to the IrisCode Theory -- Application of Correlation Filters for Iris Recognition -- Reverse Engineering the Daugman Feature Encoding Scheme -- Optics of Iris Imaging Systems.
Keywords: Computer science; Optical pattern recognition; Computer Science; Pattern Recognition